Pengembangan dan Potensi Pala (Myristica fragransi) - Alegantina, Sukmayati; Mutiatikum, D. (Jurnal Kefarmasian Indonesia, 2009)
History has shown that Indonesia is the greatest producer of nutmeg since XV century. In fact, about 60 % of the world supply of nutmeg is produce in Indonesia, where nutmegs are commonly used as both spices and food. Beside, a few use it as an oil and balsam. In other counties, nutmeg is used as material for trimiristin production, which is a main substance of myristic acid and alcohol in cosmetic industry. Data have shown that Indonesian ’s export of nutmeg to USA is rally high, especially for the nutmeg ‘s production. The price of trimiristin is relatively high when synthesized from myristic acid and alcohol. Therefore, the development of new techniques for the isolaton of timiristin from nutmeg may decrease the production costs. Furthermore, trimiristin production can be hugely increased, due to the large quantity of nutmeg produced in Indonesia.